Sea Surface Temperature Anomaly in the Bay of Bengal in 2010 - Shamsad, M; Farukh, MA; Chowdhury, MJR; Basak, SC (Journal of Environmental Science and Natural Resources, 2013)
Bangladesh is one of the most disaster prone countries in the world and is a victim of frequent natural calamities like tropical cyclones, tornadoes, floods, storm surges and droughts. Sea surface temperature (SST) plays a vital role in determining ocean-atmosphere interaction. In this study we focused on understanding the behavior of SST anomaly prevailed in the region of Bay of Bengal mainly to assume the surface temperature signature for cyclone occurrence. For this study, the observed SST anomaly data were derived from NOAA Coast-watch using a combination of global and regional algorithms. The SST anomaly maps were produced using SAGA-GIS software where the SST lines were fixed at the mean of 30 years data. The AVHRR SST was compared with the climatological SST for the region of Bay of Bengal in 2010. The monthly SST anomaly for 2010 showed average departure of 0.7°C for all the months except June and October. It was found that the anomaly increases about 2°C at the end of September, and in October the basin bears no significant anomaly. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14797 J. Environ. Sci. & Natural Resources, 5(2): 77-80 2012